2003
DOI: 10.1086/345874
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusExpress Unique Superantigens Depending on the Tissue Source

Abstract: A comprehensive analysis of Staphylococcus aureus superantigen (SAG) genes was undertaken in isolates from a major hospital and compared with isolates from patients with toxic shock syndrome (TSS). Polymerase chain reaction (PCR) analysis included recently discovered SAGs. Staphylococcal enterotoxin (SE) G and SEI were uniquely expressed in genital isolates. Genital isolates were similar to TSS isolates, although the latter frequently expressed TSS toxin 1. Both had a high frequency of SEG/SEI and a high numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…This depends on the ability of Staphylococcus aureus to produce toxins or virulence factors that facilitated the disease occurrence [42]. The S. auerus enterotoxins (SE), particular SEA-SEE were the most classical discovered genes in cattle, sheep and goats milk [1,43] Showed that the host environment played a role in the adaptation of S. auerus in target host through production of SE. Modern molecular techniques as multiplex PCR has successfully adapted for detection of enterotoxins in S. aureus isolates from subclinical mastitis milk and Karich-cheese was done in this work as showed in figure 1 and table (3).…”
Section: Discussionmentioning
confidence: 99%
“…This depends on the ability of Staphylococcus aureus to produce toxins or virulence factors that facilitated the disease occurrence [42]. The S. auerus enterotoxins (SE), particular SEA-SEE were the most classical discovered genes in cattle, sheep and goats milk [1,43] Showed that the host environment played a role in the adaptation of S. auerus in target host through production of SE. Modern molecular techniques as multiplex PCR has successfully adapted for detection of enterotoxins in S. aureus isolates from subclinical mastitis milk and Karich-cheese was done in this work as showed in figure 1 and table (3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that different types of SEs have different emetic response activities in house musk shrews, although it was thought that there are no differences in the emetic response activities of SEA, SEB, SEC, SED, and SEE in humans and primates (18). In addition, S. aureus expression of specific ent genes may depend on the host tissue and may play a role in the adaptation of S. aureus to the host environment (4). Some have speculated that some cases of food poisoning result from the simultaneous expression of several enterotoxins in a single pathogenic S. aureus strain rather than from the expression of a single toxin.…”
Section: Vol 42 2004 Simultaneous Analysis Of Multiple Se Genes 2141mentioning
confidence: 99%
“…These toxins may be involved in modulating the host immune response and may contribute to evasion of host defenses and bacterial persistence (12). Expression of specific enterotoxin (ent) genes by Staphylococcus aureus depends on the host tissue source and may play a role in the adaptation of S. aureus to the host environment (4).…”
mentioning
confidence: 99%
“…S. aureus is one of the most frequent causes of hospital-acquired infections, and the emergence and spread of multiresistant strains give rise to concern. The pathogenicity of S. aureus is multifactorial, and the versatility of this organism is underscored by recent clinical studies (4,14,16,31,37,38).Superantigens activate large subpopulations of T lymphocytes by directly cross-linking certain T-cell receptor V␀ domains with conserved structures on major histocompatibility complex class II molecules (32). They belong to the most potent T-cell mitogens known and can induce massive systemic cytokine release, leading to the symptoms of toxic shock syndrome (22).…”
mentioning
confidence: 99%
“…S. aureus is one of the most frequent causes of hospital-acquired infections, and the emergence and spread of multiresistant strains give rise to concern. The pathogenicity of S. aureus is multifactorial, and the versatility of this organism is underscored by recent clinical studies (4,14,16,31,37,38).…”
mentioning
confidence: 99%